Anytime Algorithm of Database Tuning Advisor for Microsoft SQL Server - Chaudhuri, Surajit; Narasayya, Vivek (2020)
This article provides an overview of the algorithm used by the Database Engine Tuning Advisor (DTA) in Microsoft SQL Server. While many aspects of these algorithms have been described in published papers, in this article we capture the algorithm end-to-end and include a few additional details. One goal of this article is to share with the database community the algorithm and make it easier for researchers intending to compare different approaches to physical design tuning. Note that several patents have been issued to Microsoft that protects its intellectual rights for commercial use of this algorithm.